Social protection as a right of people affected by tuberculosis - Ferreira, Melisane Regina Lima (2023)
Funding Information: The present work was carried out with the support of the Coordenação de Aperfeiçoamento de Pessoal de Nível Superior —Brazil (CAPES/Brazil)—funding code 001. Funding Information: Another study conducted in Bangladesh, through a collaboration between the TB Control Program and funding from the Global Fund, introduced the reimbursement of direct costs due to TB diagnoses as a means of financial protection. This approach aimed to connect the poorest people to diagnosis and improve the detection of new cases []. Publisher Copyright: © 2023, The Author(s).